1999
DOI: 10.1074/jbc.274.25.17573
|View full text |Cite
|
Sign up to set email alerts
|

Backbone Cyclic Peptide Antagonists, Derived from the Insect Pheromone Biosynthesis Activating Neuropeptide, Inhibit Sex Pheromone Biosynthesis in Moths

Abstract: We describe an application of the backbone cyclization and cycloscan concept for the design and synthesis of pheromone biosynthesis activating neuropeptide (PBAN) antagonists capable of inhibiting sex pheromone biosynthesis in Heliothis peltigera female moths. Two backbone cyclic (BBC) sub-libraries were designed and synthesized. The structure of the first sub-library ([Arg 27 ]PBAN27-33NH 2 , termed the Ser sub-library) was based on the active C-terminal hexapeptide sequence (Tyr-Phe-Ser-Pro-Arg-Leu-NH 2 ) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 54 publications
1
28
1
Order By: Relevance
“…These parameters include ring size, position, and chemistry. The feasibility of these methodologies has been demonstrated with several naturally occurring peptides, including substance P (6,7,10,11), somatostatin (9), and pheromone biosynthesis activating neuropeptide (5), resulting in the development of receptor-selective and metabolically stable BC peptides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters include ring size, position, and chemistry. The feasibility of these methodologies has been demonstrated with several naturally occurring peptides, including substance P (6,7,10,11), somatostatin (9), and pheromone biosynthesis activating neuropeptide (5), resulting in the development of receptor-selective and metabolically stable BC peptides.…”
mentioning
confidence: 99%
“…Backbone cyclization of peptides is the method of cyclization developed and used in our lab. It results in peptides with improved selectivity, enhanced metabolic stability, and high bioavailability (5)(6)(7)(8)(9). To select the most active backbone cyclic (BC) 1 peptide based on a given sequence, we have developed the "cycloscan" technology (10), which involves the structure-based design, synthesis, and screening of BC peptide libraries.…”
mentioning
confidence: 99%
“…The hypothesis was further supported by the behavior of a library of backbone cyclic (BBC) conformationally constrained PBANderived peptides, which, because of their rigid structure are much more receptor selective. The BBC peptides, all of which have the same primary sequence, same bridge location, and chemistry but differ from each other in their bridge sizes (Altstein et al, 1999), exhibited selective agonistic and antagonistic pheromonotropic and melanotropic activities (Ben-Aziz et al, 2006). It should be noted, however, that although the above results do imply that the differing sequences in the N-terminal and extracellular region may affect the docking and interaction of the peptide ligands with the receptors, which in turn may account for the differing and selective activities of the tested peptides, the possibility that the different assay conditions accounted for the differences in bioactivity should not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of the analog DH-Jo (Ac-GLWA[Jo]RLa) was accomplished by adapting the previously described solution phase synthesis of Jones and Ward (14) to a solid phase strategy using Rink Amide resin utilizing Fmocprotected amino acids on an ABI 433A peptide synthesizer under previously described conditions (21 (17,22), and synthesis of the "head-to-tail" cyclic octapeptide DH analog cyclo[GLWFGPRL] was carried out by adopting previously described procedures (15) used for synthesis of the related cyclic pyrokinin octapeptide analog cycloLPK (cyclo [NTSFTPRL]). …”
Section: Methodsmentioning
confidence: 99%
“…The primary method utilized previously to develop antagonists to the pyrokinin/PBAN family was to use a D-Phe substitution (17,18), such as found in the PBAN antagonist PPK-AA (18). Another method for antagonist development is to incorporate β-amino acids (16,19), but our preliminary data evaluation showed that neither PPK-AA nor other compounds containing either D-Phe or both D-Phe and β-amino acids could effectively inhibit DH activity in our diapause termination assay.…”
Section: Preventing Pupal Diapause With Dh Agonists Administered To Lmentioning
confidence: 99%